Differentiating Antiproliferative and Chemopreventive Modes of Activity for Electron‐Deficient Aryl Isothiocyanates against Human MCF‐7 Cells - Anderson, Ruthellen H.; Lensing, Cody J.; Forred, Benjamin J.; Amolins, Michael W.; Aegerter, Cassandra L.; Vitiello, Peter F.; Mays, Jared R. (ChemMedChem, 2018)
The consumption of Brassica vegetables provides beneficial effects through organic isothiocyanates (ITCs), products of the enzymatic hydrolysis of glucosinolate secondary metabolites. The ITC l‐sulforaphane (l‐SFN) is the principle agent in broccoli that demonstrates several modes of anticancer action. While the anticancer properties of ITCs like l‐SFN have been extensively studied and l‐SFN has been the subject of multiple human clinical trials, the scope of this work has largely been limited to those derivatives found in nature. Previous studies have demonstrated that structural changes in an ITC can lead to marked differences in a compound's potency to 1) inhibit the growth of cancer cells, and 2) alter cellular transcriptional profiles. This study describes the preparation of a library of non‐natural aryl ITCs and the development of a bifurcated screening approach to evaluate the dose‐ and time‐dependence on antiproliferative and chemopreventive properties against human MCF‐7 breast cancer cells. Antiproliferative effects were evaluated using a commercial MTS cell viability assay. Chemopreventive properties were evaluated using an antioxidant response element (ARE)‐promoted luciferase reporter assay. The results of this study have led to the identification of 1) several key structure–activity relationships and 2) lead ITCs for continued development. Broccoli improved: Eating Brassica vegetables provides beneficial effects via organic isothiocyanates (ITCs). The ITC l‐sulforaphane (1) is the principle agent in broccoli that demonstrates several modes of anticancer action. Modifications to ITCs can alter their antiproliferative activities, and we report SAR data revealing how ITCs can be made more potent. Shown is a sample dose–response plot of 1 against MCF‐7 cells after treatment for 24 (dashed lines) and 72 h (solid lines).